Analysis of Factors Affecting the Timeliness of Financial Statement Submission - Fira Alya Putri; Wiwi Idawati; Dwi Jaya Kirana (Indonesia Banking School, 2021)
The purpose of this study to examine the effect of Profitability, Firm Size, Auditor’s Opinion, Reputation of Public Accounting Firm on Timeliness Reporting Financial Statement. In this study Logistic Regression is carried out with significance 5% on 39 sample of mining companies on the IDX during period 2017-2019. Profitability is measured by ROE, Firm Size is measured by ln asset total, Audit’s Opinion and Rep-utation of Public Accounting Firm are measured by dummy variable. This research showed that (1) Profita-bility has no significant effect on Timeliness Reporting Financial Statement, (2) Firm Size has no signifi-cant effect on Timeliness Reporting Financial Statement, (3) Auditor’s Opinion has significant effect on Timeliness Reporting Financial Statement and (4) Reputation of Public Accounting Firm has significant effect on Timeliness Reporting Financial Statement.